The Concept of Electronic-Based THIS Planning in the Ministry of Transportation - Irwan Dharmawan (The Journal of Indonesia Sustainable Development Planning, 2023)
Synchronization of planning and budgeting is a common problem that is often experienced by public organizations in Indonesia, especially in the Ministry of Transportation. The gap in planning and implementation due to this problem is a symptom that the THIS (Thematic, Holistic, Integrative, Spatial) concept has not been able to run optimally and could be optimized through e-government, which does actually not yet reflect the interoperability aspects between each planning application such as e-planning & budgeting; e-performance; e-monitoring & reporting; up to ap2kp (Aplication for Appraisal of Achievement and Calculation of Empoyee Performance). This study uses a qualitative approach with a case study method strengthened by an Analytical Hierarchy Process to examine the application of the electronic-based THIS concept. The results of this study provide policy advices for the preparation of a new ministerial regulation about integrated planning and develop a business process related to the planning flow within the Ministry of Transportation which accommodates the THIS concept.